Development of Learning Media for Creed and Morals Based On the Prezi Application - Pohan, Abdul Hakim; Sepriyanti, Nana; Marhamah, Marhamah; Remiswal, Remiswal; Hasnah, Radhiatul (An-Nuha, 2025)
This research is motivated by the low learning outcomes of Akidah Akhlak. Among the causal factors are that learning is still conventional, there is no Prezi learning media used, the media used is less relevant, students feel that learning is less interesting so they feel bored, fall asleep and look for other activities, students are less able to improve critical thinking in themselves. This study aims to determine the validity, practicality and effectiveness of the Akidah Akhlak learning media. This research is a Research and Development (R&D) with a 4-D model, namely: defining, planning (design), developing (develop) and disseminating (Dissemination). However, due to limited research capabilities and time, in this study the researcher only reached the third stage (3-D), namely: defining stage (define), planning stage (design), and development stage (develop). Based on the validation results, material experts got very valid criteria with a percentage of (98.3%). Language experts got valid criteria with a percentage of 85%. And media experts got valid criteria with a percentage of 86.3%. And the practicality results of the three teachers showed a percentage of 95.55% with a very practical category. And for the practicality results of students in small-scale trials, they got a percentage of 95.32% with a very practical category and in large-scale product tests on students, 96.95% were obtained with a very practical category. The learning outcomes of students in the experimental class were tested with questions (pretest and posttest) analyzed with the N-Gain test, getting a result of 0.78 and included in the high criteria. The learning outcomes of students in the control class were tested with questions (pretest and posttest) analyzed with the N-Gain test, getting a result of 0.3